Pelaksanaan Konseling Multikultural dalam Penyelesaian Konflik Mahasiswa UIN SYAHADA Padangsidimpuan - Arifin Hidayat; Nurintan Muliani Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2026)
This study aims to analyze the implementation of multicultural counseling in resolving conflicts among students at UIN Syahada Padangsidimpuan. The diversity of students' cultural, ethnic, linguistic, religious, and social backgrounds represents both an asset and a potential source of conflict if not managed appropriately. Multicultural counseling serves as a relevant approach to help students understand differences, cultivate tolerance, and resolve conflicts constructively. This literature review employs the SPIDER framework, which—according to Methley—is applicable to qualitative research, other methods, or mixed-method approaches. SPIDER stands for Sample, Phenomenon of Interest, Design, Evaluation, and Research type. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was verified using source and method triangulation techniques. The results indicate that multicultural counseling at UIN Syahada Padangsidimpuan is implemented through stages involving problem identification, needs assessment, individual and group counseling sessions, conflict mediation, and follow-up evaluation, all while prioritizing values such as mutual respect, empathy, fairness, and dialogic communication. This approach has proven effective in raising student awareness regarding the importance of respecting diversity, reducing prejudice and stereotypes, improving interpersonal relationships, and fostering a more harmonious and inclusive academic environment. However, implementation still faces various challenges, such as limited counselor competence regarding multicultural issues, low awareness among some students, and suboptimal institutional support programs. Therefore, there is a need to strengthen counselor capacity, integrate multicultural education into student activities, and secure campus policy support to optimize conflict resolution based on multicultural counseling.